The New Zealand Centre for Adverse Reactions Monitoring: a source of practice-based evidence - Savage R (CSIRO Publishing, 2013)
The database of the New Zealand Centre for Adverse Reactions Monitoring (CARM) is an example of the practice-based evidence discussed in the June issue of the Journal of Primary Health Care. Databases of reported adverse drug reactions (ADRs) were established to generate hypotheses to be tested about previously unrecognised adverse reactions and interactions. Occasionally they are sufficient evidence in themselves. They can also identify prescribing practices that might increase the potential for ADRs to occur and provide feedback into guidelines in terms of the consequences of their use or non-use. Well-documented ADR reports can also highlight risk factors, thus providing a valuable contribution to risk benefit assessments in individual patients. Examples are discussed that support the use of ADRs as practice-based evidence in a non-hierarchical system in which case reports and case series, observational studies and randomised clinical trials contribute in a flexible relationship depending on the issue under investigation.